Early talk boost: A targeted intervention for three year old children with delayed language development. (February 2018) - Reeves, Louisa; Hartshorne, Mary; Black, Rachael; Atkinson, Jill; Baxter, Amanda; Pring, Tim
Pre-school education has been greatly expanded in the United Kingdom in the last two decades and further expansion is planned. Its provision allows parents to take up employment thus increasing family incomes and it is expected to narrow the gap between socially disadvantaged children and their peers. The latter is important as studies have shown that many children start school with poor language skills which threaten their attainment. Studies of the effects of pre-school education on the progress of disadvantaged children have shown inconsistent results and nurseries have been criticised by Ofsted for failing to prepare children for school entry. Nurseries and their staff have been found to vary in quality and in the level of qualifications they have. The provision of evidence based programmes which nursery staff may be trained to use may represent one means of improving their ability and improving the outcomes for pre-school children. We report an effectiveness study of Early Talk Boost a programme for use by nursery staff to improve language skills in three year olds. Nurseries were randomly assigned to use the programme or to act as waiting controls (who received the intervention in the following term). Children were assessed before and three months later after the completion of the programme. The progress of treated and control children differed significantly. Age equivalent scores showed treated children had gained 4.93 months, control children had gained only 2.33 months. We conclude that Early Talk Boost can be effective in advancing the language skills of socially disadvantaged children and improve their school readiness.